2012
DOI: 10.1097/mpg.0b013e31823e98c2
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cystatin C Correlates Negatively With Viral Load in Treatment‐naïve Children With Chronic Hepatitis C

Abstract: Cystatin C levels correlated negatively with HCV viremia. This finding may reflect an inhibitory effect of cystatin C on HCV replication through inhibiting its NS2/3 and tempting for further studies for cystatin C as a possible adjuvant therapy for HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…HCV-infected patients had significantly higher serum cystatin C (> 1.24 mg/L) and lower creatinine/cystatin C ratio (< 70.1 μMol/mg) and was correlated with renal function and extrahepatic cryoglobulins and RF and complement C3 parameters. This finding may be supported by many studies that reported the relationship between HCV infection and serum cystatin C [ 8 10 ]. The creatinine/cystatin C ratio or creatinine/cystatin C × 100 was an indicator to sarcopenia index (SI) for the prediction of liver injury and sarcopenia in liver disease [ 22 ] and monitoring the progression of non-alcoholic fatty liver disease [ 21 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…HCV-infected patients had significantly higher serum cystatin C (> 1.24 mg/L) and lower creatinine/cystatin C ratio (< 70.1 μMol/mg) and was correlated with renal function and extrahepatic cryoglobulins and RF and complement C3 parameters. This finding may be supported by many studies that reported the relationship between HCV infection and serum cystatin C [ 8 10 ]. The creatinine/cystatin C ratio or creatinine/cystatin C × 100 was an indicator to sarcopenia index (SI) for the prediction of liver injury and sarcopenia in liver disease [ 22 ] and monitoring the progression of non-alcoholic fatty liver disease [ 21 ].…”
Section: Discussionsupporting
confidence: 76%
“…Cystatin C is a potent inhibitor of lysosomal proteinases and probably one of the most important extracellular inhibitors of cysteine proteases [8][9][10]. Cystatin C has an advantage as low molecular weight (13.3 kilodaltons), produced at a constant rate in all nucleated cells, eliminated by glomerular filtration, reabsorbed, and catalyzed in renal proximal tubular cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of cystatin C may have the inhibitory effect on viral cysteine proteases (NS2/3) as suggested by Behairy et al in a study conducted in 2012, revealing that serum cystatin C levels correlated negatively with the viral load and did not fluctuate with the severity of infection. This would be of greatest importance assuming a potential role of cystatin C as an inhibitor of viral replication, because its antiviral functions have already been reported in different studies done with virus-infected cell (Behairy et al, 2012).…”
Section: Discussionmentioning
confidence: 94%